2005
DOI: 10.1191/1463423605pc206oa
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a primary care counselling service: outcomes and issues

Abstract: Mental health issues are the third most common reason for consulting a general practitioner (GP), after respiratory disorders and cardiovascular disorders (Department of Health, 1991; Hemmings, 2000). A quarter of routine GP consultations relate to people with a mental health problem, most commonly depression and anxiety. It has been estimated that each year, one in 15 women and one in 30 men will be affected by depression, and every GP will see between 60 and 100 people with depression (Department of Health, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…Incomplete data are common in routine practice settings (Stiles et al 2003 ;Gilbert et al 2005 ;Greasley & Small, 2005), and we emphasize that our conclusions are limited to patients who completed post-treatment forms. Among patients who do receive treatment, those who complete post-treatment measures are more likely to have agreed with their therapist about when treatment should end ) and more likely to have improved more during treatment (Stiles et al 2003) than are patients who fail to complete them.…”
Section: Lack Of Experimental Controlmentioning
confidence: 91%
“…Incomplete data are common in routine practice settings (Stiles et al 2003 ;Gilbert et al 2005 ;Greasley & Small, 2005), and we emphasize that our conclusions are limited to patients who completed post-treatment forms. Among patients who do receive treatment, those who complete post-treatment measures are more likely to have agreed with their therapist about when treatment should end ) and more likely to have improved more during treatment (Stiles et al 2003) than are patients who fail to complete them.…”
Section: Lack Of Experimental Controlmentioning
confidence: 91%
“…Moreover, that evidence which exists is largely inconclusive or conflicting, and restricted in focus (Vedsted & Christensen, 2005). For instance, the lack of accord between existing research findings on psychological outcomes can be illustrated by the following examples: Ward et al (2000), The NHS Centre for Reviews and Dissemination (2001), Greasley and Small (2005) and Bower et al (2003) all found that counselling was more effective than standard GP care in the short term for patients with mental health problems, although the benefits had typically disappeared after twelve months. On the other hand, Beecham (2003a, 2003b) found very little evidence of improved outcomes for patients suffering from chronic depression or other mental health problems, while Baker et al (1998) …”
Section: Introductionmentioning
confidence: 95%
“…One approach has been to focus on those patients who make heavy claims on GP time, such as frequent attenders (FAs) and those patients for whom the primary problems are psychological in origin (e.g. Greasley & Small, 2005). A considerable amount of research attention has been particularly directed to FAs, whose problems are often complex, with high levels of physical, psychological and social morbidity (Vedsted & Christensen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, both unmet need for and fit of primary medical services in a PHC system, such as those provided by a family doctor, general practice physician, or nurse practitioner, have been associated with early detection of illness and disease, resulting in better mental and physical health outcomes (Bindman, Grumbach, Osmond, Vranzian, & Stewart, 1996;Shi, 1994;Shi et al, 2004;Vogel & Ackerman, 1998). Moreover, patients who access mental health services in PHC settings, such as those provided by counselors, social workers, psychologists, and psychiatric nurses, without the requirement of a referral, report significant improvements in depressive symptoms, anxiety, self-esteem, and quality of life over time (Baker et al, 2002;Greasley & Small, 2005;Nettleton et al, 2000). Few Canadian researchers, however, have examined the impact of either unmet need or fit of PHC services on the mental and physical health of Canadians, including women who have experienced IPV.…”
Section: Introductionmentioning
confidence: 99%